A long-term cohort study of the muscle apparatus of female volleyball players after the application of a compensatory programme - Cucková, T.; Süss, V.; Carboch, J. (AUC Kinanthropologica, 2017)
Volleyball is a sport with great unilateral load that can have a negative impact on a postural system. The aim of the study was to perform a detailed examination of posture and muscle imbalance in elite female volleyball athletes and, according to the results of the examination, to put together compensatory exercises and to assess their effect. A group of elite junior female volleyball players (n = 12) was examined by an experienced physiotherapist using a complex kinesiological analysis especially focused on body posture (from frontal, sagittal and dorsal plane), shortened muscles and performance of basic movement patterns (hip extension, hip abduction, sit-up, cervical flexion, shoulder abduction, push-up). The preliminary examination showed that every tested player had some kind of posture deficiency. The compensatory programme, consisting of breathing techniques, stretching exercises, strengthening exercises with an elastic band, and balance exercises with a Bosu balance trainer, was applied at the end of every training session over the competitive parts of two volleyball seasons. Before the application of the exercise programme we found flat back in 92% subjects, whereas 33% of subjects exhibited it after compensation. Improvement was noted in the intensified lumbar lordosis (from 50% subjects to 42%), and scoliotic body posture (from 50% to 17%). The biggest improvement in shortened muscles in the upper body was observed on the m. levator scapulae (from 83% subjects to 8%) and the m. trapezius (from 42% subjects to 8%); and in the lower body m. triceps surae (from 75% subjects to 33%) and hip abductors (from 83% subjects to 25%). The study suggests that balance exercises with a Bosu balance trainer and exercises with an exercise elastic band seem to be useful for volleyball since we noted improvement in body posture, movement patterns and muscle shortness. We therefore highly recommend this compensatory programme.